1991
DOI: 10.1159/000163647
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cytokine and Viral Gene Expression in Monocytes Infected with the Human Immunodeficiency Virus

Abstract: Monocytes treated with interferon-α (IFN-α) at virus challenge show no evidence of human immunodeficiency virus (HIV) infection: no p24 antigen or reverse transcriptase (RT) activity, no viral mRNA and no proviral DNA. Levels of p24 antigen and RT activity in monocytes infected with HIV 1–3 weeks before IFN-α treatment gradually decrease to baseline. HIV-induced cytopathic changes are markedly reduced, as are levels of HIV mRNA: the frequency of productively infected cells is ≤ 1 %. But, levels of proviral DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…We report that HIV-1-induced ROS and cathepsin B were required for the activation of the NLRP3 inflammasome. It has been reported previously that there are no differences in the IL-1␤ pattern in HIV-1-infected versus non-infected monocytes (47)(48)(49). The discrepancy is probably due to the different HIV-1 strains or the lower multiplicity of infection used in previous experiments.…”
Section: Discussionmentioning
confidence: 79%
“…We report that HIV-1-induced ROS and cathepsin B were required for the activation of the NLRP3 inflammasome. It has been reported previously that there are no differences in the IL-1␤ pattern in HIV-1-infected versus non-infected monocytes (47)(48)(49). The discrepancy is probably due to the different HIV-1 strains or the lower multiplicity of infection used in previous experiments.…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, the reduced virus production may have resulted from inhibition of the development of macrophage precursors into macrophages. Previous studies have shown that lentivirus production in PBMC correlated with development of macrophages in the cultures (16,62), and virus production in these cells is contingent upon transcriptional activation factors that are produced by macrophages but not their precursors (15,55). Both monocytes and dendritic cells in PBMC give rise to phagocytic, adherent macrophages in culture (3, 34,64).…”
Section: Discussionmentioning
confidence: 99%
“…This pattern has been previously observed in HIV infected monocytes. While they have an impaired ability to produce interferon alpha, production of interferon beta remains normal (20). …”
Section: Discussionmentioning
confidence: 99%
“…It is thought that this mechanism is responsible for the down regulation of both viral and cytokine gene expression (9). Although the production of interferon beta usually leads to the production of interferon alpha, it has been reported that HIV infected monocytes have a reduced ability to produce interferon alpha while interferon beta levels remain the same (20). This implies that differential interferon signaling patterns may exist, which may not be surprising since interferon alpha and beta have been shown to have different activities, especially in the CNS (21).…”
Section: Introductionmentioning
confidence: 99%